Algebra
-
If m4 + 1 = 119 , then m - 1 = ? m4 m
-
View Hint View Answer Discuss in Forum
m4 + 1 = 119 m4 ⇒ m2 + 1 2 - 2 = 119 m2 ⇒ m2 + 1 2 = 119 + 2 = 121 m2 ⇒ m2 + 1 = 11 m2 ⇒ m - 1 2 + 2 = 11 m ⇒ m - 1 2 = 11 – 2 = 9 m ⇒ m - 1 = ± 3 m Correct Option: A
m4 + 1 = 119 m4 ⇒ m2 + 1 2 - 2 = 119 m2 ⇒ m2 + 1 2 = 119 + 2 = 121 m2 ⇒ m2 + 1 = 11 m2 ⇒ m - 1 2 + 2 = 11 m ⇒ m - 1 2 = 11 – 2 = 9 m ⇒ m - 1 = ± 3 m
-
If x - 1 = 3 , then the value of x3 - 1 is x x3
-
View Hint View Answer Discuss in Forum
Using Rule 9,
x - 1 = 3 x
On cubing both sides,⇒ x - 1 3 = 27 x ⇒ x3 - 1 - 3 x - 1 = 27 x3 x ⇒ x3 - 1 - 3 × 3 = 27 x3 ⇒ x3 - 1 = 27 + 9 = 36 x3 Correct Option: B
Using Rule 9,
x - 1 = 3 x
On cubing both sides,⇒ x - 1 3 = 27 x ⇒ x3 - 1 - 3 x - 1 = 27 x3 x ⇒ x3 - 1 - 3 × 3 = 27 x3 ⇒ x3 - 1 = 27 + 9 = 36 x3
-
If x + 1 = 3 , then the value of x5 + 1 is x x5
-
View Hint View Answer Discuss in Forum
Using Rule 1 and 8,
x + 1 2 = x2 + 1 + 2 x x2 ⇒ x2 + 1 = 9 - 2 = 7 x2
Again ,x + 1 3 = x3 + 1 + 3 x + 1 x x3 x ⇒ 27 = x3 + 1 + 3 × 3 x3 ⇒ x3 + 1 = 18 x3 ∴ x2 + 1 x3 + 1 = 7 × 18 = 126 x2 x3 ⇒ x5 + x + 1 + 1 = 126 x x5 ⇒ x5 + 1 = 126 – 3 = 123 x5 Correct Option: C
Using Rule 1 and 8,
x + 1 2 = x2 + 1 + 2 x x2 ⇒ x2 + 1 = 9 - 2 = 7 x2
Again ,x + 1 3 = x3 + 1 + 3 x + 1 x x3 x ⇒ 27 = x3 + 1 + 3 × 3 x3 ⇒ x3 + 1 = 18 x3 ∴ x2 + 1 x3 + 1 = 7 × 18 = 126 x2 x3 ⇒ x5 + x + 1 + 1 = 126 x x5 ⇒ x5 + 1 = 126 – 3 = 123 x5
-
If x is real, x + 1 ≠ 0 and x3 + 1 = 0 , then the value of x + 1 4 is x x3 x
-
View Hint View Answer Discuss in Forum
Using Rule 8
x + 1 3 = x3 + 1 + 3 x + 1 x x3 x = 3 x + 1 x ⇒ x + 1 2 = 3 x ∴ x + 1 4 = 3 × 3 = 9 x Correct Option: B
Using Rule 8
x + 1 3 = x3 + 1 + 3 x + 1 x x3 x = 3 x + 1 x ⇒ x + 1 2 = 3 x ∴ x + 1 4 = 3 × 3 = 9 x
-
If x + 1 = 5 , then the value of x4 + 3x3 + 5x2 + 3x + 1 x x4 + 1
-
View Hint View Answer Discuss in Forum
Using Rule1 and 8,
⇒ x + 1 = 5 x
On squaring both sides,⇒ x2 + 1 + 2 = 25 x2 ⇒ x2 + 1 = 25 - 2 = 23 ...(i) x2
Expression= x4 + 3x3 + 5x2 + 3x + 1 x4 + 1 = x4 + 1 + 3x3 + 3x + 5x2 x4 + 1 = 23 + 3 × 5 + 5 = 43 23 23
Correct Option: A
Using Rule1 and 8,
⇒ x + 1 = 5 x
On squaring both sides,⇒ x2 + 1 + 2 = 25 x2 ⇒ x2 + 1 = 25 - 2 = 23 ...(i) x2
Expression= x4 + 3x3 + 5x2 + 3x + 1 x4 + 1 = x4 + 1 + 3x3 + 3x + 5x2 x4 + 1 = 23 + 3 × 5 + 5 = 43 23 23